Hope in a Time of Civicide: regenerative development and IPAT - Newman, Peter (Springer (BMD), 2020)
This paper is written as the world faces economic recovery after the Covid pandemic collapse. It also responds to the article in Sustainable Earth by Peter Hancock ‘In Praise of Civicide’ by creating a more hopeful vision of the future. Peter suggests the only hope is in psychological mind-sets that can change behaviour as nothing else will stop the path to destruction from present growth in population, the economy and technology. Rather than seeing inevitable civicidal elements, as devised in the IPAT model used by Peter and many others to explain global environmental destruction, the paper reassesses the fundamentals of this model developed by Paul and Anne Ehrlich in the 1960's. As the global economy has collapsed and environmental impacts improved everywhere, the Hancock argument based on IPAT would seem to have support. The paper shows how it is possible to grow again in the three IPAT factors if the world moves beyond sustainable development which just minimises impact to regenerative development which reclaims environmental impacts. If all three elements combine to create uncontrolled growth as was happening in the 60’s to 80’s then civicide is inevitable, but not if they change to regenerative development. The three stages of exploitive, sustainable and regenerative development turn IPAT from being negative to positive about civilization. These choices are very stark in the 2020’s. The technological possibilities of a regenerative future are outlined and the fundamentals needed for a sustainable earth are sketched, providing some evidence of hope for using the present pandemic and economic collapse as the basis for regenerating civilization not praising civicide.